PROBLEMA QIRÂ’ÂT DALAM AL-QUR’AN PERSPEKSTIF MUḤAMMAD SHAḤRÛR - Fauzi, Ahmad (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2019)
The majority of Muslim scholars have agreed that al- Qirā’āt al-Sab῾ or al- Qirā’āt al-‘Asyr is a ṣaḥῑḥah (valid) and acceptable qirā’āt. The variety in reading the Qur’an is believed to be part of al-Aḥruf al-Sab῾ah which was revealed to the Prophet Muhammad SAW. In contrast to this view, Muḥammad Syaḥrūr had analysed various kinds of qirā’ah through contemporary reading. Syaḥrūr indicated that there was an error that occured when giving syakal and i῾rāb to the texts of al-Tanzῑl al-Ḥakῑm the HolyQur’an. He justified that the error was ocured due to human error which then contributed greatly to the emergence of different pronunciation in the future. This study examines the perspective of Syahrur towards qirā’āt, in which researcher have found that Syaḥrūr’s perspective about qirā’āt is only assumption with lack of scientific evidence. Syaḥrūr has missed several aspects within his study towards parts of qirā’ah, for example the strict sanad lines through the history of a qirā’ah which was obtained through analytic descriptive and historical methods. There is also found that Syaḥrūr’s opinion was influenced by perspective of Western scholars (orientalists) who also doubted the authenticity of qirā’āt, even though he did not explain this. Keywords: Muhammad Shahrur, qira’at, al-ahruf al-sab῾ah, shakl.